Schreber's Law : Jurisprudence and Judgment in Transition - Goodrich, Peter, 1954- (Edinburgh critical studies in law, literature and the humanities., 2018)
Peter Goodrich looks beyond Judge Schreber's mental health to evaluate his jurisprudential theory. Goodrich analyses Schreber's Memoirs, interpreters and intellectual context to show how Schreber challenges the legal thought of his era and opens up a potentially vital approach to contemporary jurisprudence.